Novel prospects for scarless wound healing: The roles of myofibroblasts and adipocytes. Issue 20 (15th September 2022) - Teng, Ying‐Ying; Zou, Ming‐Li; Zhou, Xiao‐Jin; Wu, Jun‐Jie; Liu, Si‐Yu; Yuan, Zheng‐Dong; Jia, Yuan; Zhang, Kai‐Wen; Li, Xia; Ye, Jun‐Xing; Yuan, Feng‐Lai
Abstract: Disturbances or defects in the process of wound repair can disrupt the delicate balance of cells and molecules necessary for complete wound healing, thus leading to chronic wounds or fibrotic scars. Myofibroblasts are one of the most important cells involved in fibrotic scars, and reprogramming provides a potential avenue to increase myofibroblast clearance. Although myofibroblasts have long been recognized as terminally differentiated cells, recent studies have shown that myofibroblasts have the capacity to be reprogrammed into adipocytes. This review intends to summarize the potential of reprogramming myofibroblasts into adipocytes. We will discuss myofibroblast lineage tracing, as well as the known mechanisms underlying adipocyte regeneration from myofibroblasts. In addition, we investigated different changes in myofibroblast gene expression, transcriptional regulators, signalling pathways and epigenetic regulators during skin wound healing. In the future, myofibroblast reprogramming in wound healing will be better understood and appreciated, which may provide new ideas for the treatment of scarless wound healing.